A Dynamic Assessment of Children’s Physical Competence - Kelly Mackintosh (Medicine & Science in Sports & Exercise, 2018)
Purpose The first aim was to develop a dynamic measure of physical competence that requires a participant to demonstrate fundamental, combined and complex movement skills, and for assessors to score both processes and products (Dragon Challenge; DC). The second aim was to assess the psychometric properties of the DC in 10–14 year old children.Methods The first phase involved the development of the DC, including the review process that established face and content validity. The second phase used DC surveillance data (n=4,355; 10–12 years) to investigate construct validity. In the final phase, a convenience sample (n=50; 10–14 years) performed the DC twice (one-week interval), the Test of Gross Motor Development-2 (TGMD-2), and the Stability Skills Assessment (SSA). This data was used to investigate concurrent validity, and test-retest, inter-rater and intra-rater reliability.Results In support of construct validity, boys (P < 0.001) and secondary school children (P < 0.001) obtained higher DC total scores than girls and primary school children, respectively. A principal component analysis revealed a nine-component solution, with the three criteria scores for each individual DC task loading onto their own distinct component. This nine-factor structure was confirmed using a confirmatory factor analysis. Results for concurrent validity showed that there was a high positive correlation between DC total score and TGMD-2 and SSA overall score (r(43) = .86, P < 0.001). DC total score showed good test-retest reliability (ICC = 0.80; 95%CI: 0.63, 0.90; P < 0.001). Inter- and intra-rater reliability on all comparison levels was good (all ICCs > .85).Conclusion The DC is a valid and reliable tool to measure elements of physical competence physical competence in children aged 10–14 years.